Systemic Administration of Orexin a Loaded Liposomes Potentiates Nucleus Accumbens Shell Dopamine Release by Sucrose Feeding - Lai, Francesco; Cucca, Flavia; Frau, Roberto; Corrias, Francesco; Schlich, Michele; Caboni, Pierluigi; Fadda, Anna Maria; Bassareo, Valentina (Frontiers in Psychiatry, 2018)
Orexin neurons originate in the lateral and dorsomedial hypothalamus and perifornical area and produce two different neuropeptides: orexin A (OxA) and orexin B (OxB), which activate OxR1 and OxR2 receptors. In the lateral hypothalamus (LH) orexin neurons are involved in behavior motivated by natural rewards such as palatable food (sugar, high-fat food) and it has been demonstrated that similarly the orexin signaling in the ventral tegmental area (VTA) is implicated in the intake of high-fat food. The VTA is an important area involved in the reward processing. Given the involvement of nucleus accumbens (NAc) shell dopamine (DA) in motivation for food, we intended to investigate the effect of OxA on the basal and feeding-activated DA transmission in the NAc shell. OxA is a large peptide and does not cross the blood–brain barrier and for this reason was loaded on two kinds of liposomes: anti-transferrin-monoclonal antibodies (OX26-mAb) and lactoferrin-modified stealth liposomes. The effect of i.v. administration of both OxA liposomes on NAc shell DA was studied by microdialysis in freely moving rats. OxA, administered using both kinds of liposomes, produced a delayed and transitory increase in dialysate DA in the NAc shell, strongly and lastingly potentiated the increase in dialysate DA elicited by sucrose pellets consumption and increased the number of eaten pellets. These effects of OxA on DA transmission and feeding were prevented by the OxR1 antagonist SB 334867. Hence, OxA acting on VTA OxR1 can facilitate sucrose-stimulated NAc shell DA transmission directly by increasing the basal activity of VTA DA neurons that send their projections to the NAc shell.